UJI POLIMORPIK DAN HETEROZIGOSITAS PADA PROGENI F4 KEDELAI (Glycine max (L.) Merril) TAHAN SALIN DENGAN MENGGUNAKAN MARKA SSR (Simple Sequence Repeats) - Evi Julianita Harahap; Rosmayanti Rosmayanti; Diana Sofia Hanafiah (Jurnal Agrotek Lestari, 2020)
SSR marker has some merits such as quickness, simplicity, rich polymorphism and stability, thus being widely applied in genetic diversity analysis, molecular map construction and gene mapping. the purpose of this study was to determine polymorpic test and heterozygosity in F4 soybean (Glycine max (L.) Merril) progeni saline resistant characters using SSR (Simple Sequence Repeats) markers. This research was conducted in Biomolecular Laboratory, Socfindo Seed Production Laboratory (SSPL), Kebun Bangun Bandar Village Martebing District Dolok Masihul Regency Serdang Bedagai on December-May 2017. The number of samples were used 44. The five SSR primers (QS080465, QS1101, QS1112, QS100011, and Sat_091) used were specific primers, with a band pattern that was clearly visible around one or two bands. The percentage of polymorphic primers (PLP) of these three populations is high, all populations with a PLP of 100% of the saline resistant character. The effective allele number (Ne) of  7,160 for the progeny population is lower than the number of observed alleles (Na) of 10,000 which means that many progeny individuals are homozygous. The expected heterozygosity (He) value of 0.854 in the progeny population was higher than the observed heterozygosity (Ho) value of 0.027. The overall average observed heterozygosity (Ho) was 0.009 lower than the overall expected heterozygosity (He) of 0.61. This means that each character has a low heterozygosity.Keywords: Progeny F4, soybean, SSR, saline resistant, polymorphic, heterozygosity